New therapeutic modalities to modulate orthodontic tooth movement - Ildeu Andrade Jr; Ana Beatriz dos Santos Sousa; Gabriela Gonçalves da Silva (Dental Press Editora, 2014)
Modulation of orthodontic tooth movement (OTM) is desirable not only to patients because it shortens treatment time, but also to orthodontists, since treatment duration is associated with increased risk of gingival inflammation, decalcification, dental caries, and root resorption. The increased focus on the biological basis of tooth movement has rendered Orthodontics a more comprehensive specialty that incorporates facets of all fields of medicine. Current knowledge raises the possibility of using new therapeutic modalities for modulation of OTM, such as corticotomy, laser therapy, vibration (low-intensity pulsed ultrasound), local injections of biomodulators and gene therapy; with the latter being applicable in the near future. They are intended to enhance or inhibit recruitment, differentiation and/or activation of bone cells, accelerate or reduce OTM, increase stability of orthodontic results, as well as assist with the prevention of root resorption. This article summarizes recent studies on each one of these therapeutic modalities, provides readers with information about how they affect OTM and points out future clinical perspectives.